Graptofaunas del Miembro Salto Macho, formación La Chilca (Ordovícico Superior-Silúrico Inferior), en la quebrada Poblete Norte, Precordillera Central de San Juan, Argentina - López, Fernando Enrique (2020)
Graptolite faunas are documented at the Salto Macho Member of the La Chilca Formation, Poblete Norte Creek, Central Precordillera of San Juan Province. This formation consists of a fine grained siliciclastic deposit composed by yellowish gray sandstones and shales. The identified graptolite fauna consists of Lagarograptus praeacinaces Cuerda, Rickards and Cingolani, Normalograptus normalis (Lapworth), Metabolograptus persculptus (Elles and Wood), Normalograptus acceptus (Koren and Mikhailova), Atavograptus atavus Jones, Monograptus cf. priodon (Bronn) and Monograptus sp., and represents the Upper Ordovician (Upper Hirnantian) and Lower Silurian (Middle-Upper Rhuddanian). The graptolite assemblage allows us to record the Metabolograptus persculptus Zone (Upper Hirnantian) and the possible Atavograptus atavus Zone (Middle-Upper Rhuddanian) at the Salto Macho Member of the La Chilca Formation. The presence of M. cf. M. priodon in the upper levels of the Salto Macho Member of the La Chilca Formation would indicate a Lower Telychian age for these levels. Also, the extension range of L. praeacinaces that reaches upper Hirnantian levels is confirmed in this study. A brachiopod assemblage and scolecodonts were recognized together with graptolite fauna on the bedding planes from the studied Member. The present contribution deals with the graptolite taxonomy, biostratigraphy and biostratigraphic correlation with the Ancha Creek, Cerro del Fuerte and Baños de Talacasto sections from the Argentine Precordillera.